Effect of creatine loading on oxygen uptake during a 1-km cycling time trial - de Andrade Nemezio, K. M.; Bertuzzi, R.; Correia-Oliveira, C. R. (Medicine & Science in Sports & Exercise, 2015)
Purpose: For the first time, we investigated the effects of altering cellular metabolic capacitance, via a 5-d creatine (Cr) loading protocol (20 g/d), on oxygen uptake (V.O2), accumulated oxygen deficit, muscle recruitment, and performance during a 1-km cycling time trial.